2011
DOI: 10.1038/leu.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

CD40 stimulation sensitizes CLL cells to rituximab-induced cell death

Abstract: In vitro CD40-stimulated chronic lymphocytic leukemia (CLL) cells are resistant to cytotoxic drugs. In sharp contrast, we here show that CD40 stimulation sensitizes CLL cells to rituximabmediated cell death. This increased sensitivity is specific for anti-CD20 treatment. Rituximab-mediated death in CD40-stimulated CLL cells shows rapid kinetics (within hours), and is caspase and p53 independent, but depends on extracellular Ca 2 þ and reactive oxygen species (ROS) production. By increasing basal ROS production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 57 publications
2
31
0
Order By: Relevance
“…Indeed, it would appear that increased expression of these molecules on the surface of CLL cells may even augment blinatumomab-directed T-cell activation and, ultimately, CLL cell killing (Online Supplementary Figure S2). These findings are in agreement with recent studies demonstrating the enhancing effect of CD40 stimulation on cytotoxicity mediated by rituximab 46 and GA101 47 antibodies. Five of the samples analyzed in this study were derived from patients with relapsed or refractory CLL with one patient also exhibiting a p53 deletion.…”
supporting
confidence: 83%
“…Indeed, it would appear that increased expression of these molecules on the surface of CLL cells may even augment blinatumomab-directed T-cell activation and, ultimately, CLL cell killing (Online Supplementary Figure S2). These findings are in agreement with recent studies demonstrating the enhancing effect of CD40 stimulation on cytotoxicity mediated by rituximab 46 and GA101 47 antibodies. Five of the samples analyzed in this study were derived from patients with relapsed or refractory CLL with one patient also exhibiting a p53 deletion.…”
supporting
confidence: 83%
“…23 Of note, whereas the ROS scavenger NAC significantly inhibited RXL-induced cell death ( Figure 5E), no inhibition was observed in GA101-induced cell death in the presence of NAC (Figure 5E), making a role for ROS in GA101-induced cell death less likely. An important question is whether lysosomes are involved in RXLinduced cell death of CD40 stimulated CLL cells.…”
mentioning
confidence: 98%
“…21,22 Rather unexpectedly, we recently found that, in contrast to its induction of chemoresistance, CD40 stimulation enhanced sensitivity of CLL cells to rituximab via a reactive oxygen species (ROS)-dependent mechanism. 23 Because of the largely different mechanism of action of type I compared with type II anti-CD20 mAbs, we investigated in the present study whether CD40 stimulation also affects the sensitivity of CLL cells to GA101 and, if so, by what mechanism. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] However, this cross-linking can hardly be realized in vivo. It seems, although we acknowledge that the activation of more effector mechanisms may lead to improved curative effects, 7,22,25,32,33 the abovementioned immunotherapeutic mechanisms could hardly be synchronously activated by any reported anti-CD20 mAb or mAb derivative until now.…”
mentioning
confidence: 99%